Acoustic Data Analysis from Multi-Sensor Capture in Rare Singing: Cantu in Paghjella Case Study. Issue 1 (March 2015) - Crevier-Buchman, Lise; Amelot, Angélique; Kork, Samer K. Al; Adda-Decker, Martine; Audibert, Nicolas; Chawah, Patrick; Denby, Bruce; Fux, Thibaut; Jaumard-Hakoun, Aurore; Roussel, Pierre; Stone, Maureen; Vaissiere, Jacqueline; et al.
This paper deals with new capturing technologies to safeguard and transmit endangered intangible cultural heritage including Corsican multipart singing technique. The described work, part of the European FP7 i-Treasures project, aims at increasing our knowledge on rare singing techniques. This paper includes (i) a presentation of our light hyper-helmet with 5 non-invasive sensors (microphone, camera, ultrasound sensor, piezoelectric sensor, electroglottograph), (ii) the data acquisition process and software modules for visualization and data analysis, (iii) a case study on acoustic analysis of voice quality for the UNESCO labelled traditional Cantu in Paghjella . We have identified specific features for this singing style, such as changes in vocal quality, especially concerning the energy in the speaking and singing formant frequency region, a nasal vibration that seems to occur during singing, as well as laryngeal mechanism characteristics. These capturing and analysis technologies will contribute to define relevant features for a future educational platform.